Prevalence of Sarcocystosis in Buffalo Meat in Major Cities of India - Ramakrishna, C.; Vaithiyanathan, S.; Muthukumar, M.; Chatlod, L. R.; Lavanya, P.; Kulkarni , V. V. (Journal of Meat Science, 2018)
A total of 1,949 oesophagus and 355 meat samples (massetter or cervical region) collected from slaughtered buffaloes were examined by naked eye for presence of Sarcocysts (macro cysts) in different cities (Hyderabad, Mumbai, Kolkata and Delhi) of India. The overall prevalence of Sarcocysts (macro cysts) was 23.87%. A total of 102 tissue samples from oesophagus were subjected to histomorphological examination. The overall prevalence of Sarcocysts (micro cysts) was 60.78%.